Drainage of Southeast Greenland Firn Aquifer Water through Crevasses to the Bed - Poinar, Kristin; Joughin, Ian; Lilien, David; Brucker, Ludovic; Kehrl, Laura; Nowicki, Sophie (Frontiers in Earth Science, 2017)
A firn aquifer in the Helheim Glacier catchment of Southeast Greenland lies directly upstream of a crevasse field. Previous measurements show that a 3.5-km long segment of the aquifer lost a large volume of water (26,000 – 65,000 m2 in cross section) between spring 2012 and spring 2013, compared to annual meltwater accumulation of 6000 – 15,000 m2. The water is thought to have entered the crevasses, but whether the water reached the bed or refroze within the ice sheet is unknown.  We used a thermo-visco-elastic model for crevasse propagation to calculate the depths and volumes of these water-filled crevasses. We compared our model output to data from the Airborne Topographic Mapper (ATM), which reveals the near-surface geometry of specific crevasses, and WorldView images, which capture the surface expressions of crevasses across our 1.5-km study area. We found a best fit with a shear modulus between 0.2 and 1.5 GPa within our study area. We show that surface meltwater can drive crevasses to the top surface of the firn aquifer (~20 m depth), whereupon it receives water at rates corresponding to the water flux through the aquifer. Our model shows that crevasses receiving firn-aquifer water hydrofracture through to the bed, ~1000 m below, in 10–40 days. Englacial refreezing of firn-aquifer water raises the average local ice temperature by ~4°C over a ten-year period, which enhances deformational ice motion by ~50 m/yr, compared to the observed surface velocity of ~200 m/yr. The effect of the basal water on the sliding velocity remains unknown. Were the firn aquifer not present to concentrate surface meltwater into crevasses, we find that no surface melt would reach the bed; instead, it would refreeze annually in crevasses at depths <500 m. The crevasse field downstream of the firn aquifer likely allows a large fraction of the aquifer water in our study area to reach the bed. Thus, future studies should consider the aquifer and crevasses as part of a common system. This system may uniquely affect ice-sheet dynamics by routing a large volume of water to the bed outside of the typical runoff period.